Development of pig production following Vietnamese Good Animal Husbandry Practices (VietGAHP) guidelines in the area of Dien Chau District, Nghe An Province - Dang Thi Be (Vietnam National Agricultural University, 2016)
Faced with an explosion of cases of food poisoning have increased concern about food hygiene and safety of consumers as well as the management agency. Applying the standards of good agricultural practice (VietGAHP) in animal husbandry to provide fresh food market are many localities across the country encouraging. The study is conducted in Dien Chau with primary data collected from 82 livestock farmers and livestock VietGAHP often along with group discussions of 20 farms. Results showed that since 2011 the process has been applied to VietGAHP pork producers in the district, after 5 years of production processes have been applied to expand in the communes with the increase in the number of households applying as well as the total number of pigs raised under VietGAHP standards. Pig farms was initially grasp new production processes and apply good several criteria into pork producers and obtained some positive results in the economic environment as well as in raising feed. Due to objective conditions with the limited resources, most households still commit more errors in the application process into livestock VietGAHP of households. VietGAHP local products no separate marketing channels, while the criteria given VietGAHP requires more complicated factors have become factors limiting the development of pig production standards VietGAHP locality. The solution offered is the solution on the market, to raise awareness raisers, complete set of criteria besides VietGAHP measures to strengthen community supervision is recommended solutions.